Faktor-Faktor yang Berpengaruh terhadap Pembentukan Kompetensi Manajerial: Studi pada Sarjana Akuntansi di Jakarta, Surabaya, dan Malang - Christea Frisdiantara; Eka Afnan Troena; Armanu Thoyib; Suhardjono Suhardjono (Jurnal Aplikasi Manajemen, 2011)
This research aims to analisize the factors which influence towards of accountant graduates has been moderated by job-experience and professional education in managerial competence building. The methode of analysis used in this research is Partial Least Square (PLS). The data consists of primary data and secondary data. Primary data got by snow balling technique. The population and sample in this research are accountant graduates from many universities in Indonesia who have worked in many business such as Jakarta, Surabaya and Malang. Based on this analysis, this research gives some important conclusions: accountant graduates has enough competence in technical competence, but less influence in managerial competence building; job-experience influences toward managerial competence building; motivation achievement influences toward managerial competence; training will influence the managerial competence building more significant, and also accountant professional education has significant influence toward managerial competence building for accountant graduates.Keywords: Accountant Graduates Competence, Managerial Competence, Achievement Motivation, Job-Experience, Partial Least Square.